2022
DOI: 10.1017/s1754470x22000071
|View full text |Cite
|
Sign up to set email alerts
|

Use of a low frustration tolerance exercise for trainee therapists in a SP/SR framework

Abstract: Application of a self-practice self-reflection (SP/SR) framework to clinical training programmes for those learning cognitive behavioural therapy (CBT) have demonstrated positive outcomes. These programmes have typically resulted in reports of enhanced learning, improved clinical skills, heightened empathy, improved interpersonal skills, increased self-awareness, and self-development for those undertaking such training. However, the utility of specific activities within this framework for enhancing trainees’ l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Participants have typically reported a range of promising outcomes from this form of training. Amongst the benefits reported have been an enhanced confidence with, and understanding of cognitive behavioural theory, an increased appreciation for cognitive behavioural strategies, and greater skill in the application of techniques, including greater flexibility and nuance in their application (Bennett-Levy, 2019; Chigwedere et al, 2019;Collard and Clarke, 2020;Collard and Clarke, 2022;Davis et al, 2015;McGillivray et al, 2015;Scott et al, 2021). Participants also tend to report improved interpersonal skills, allowing for a greater attunement with clients and increased empathy for their presenting difficulties (Bennett-Levy et al, 2015;Chigwedere et al, 2019;McGillivray et al, 2015;Thwaites et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants have typically reported a range of promising outcomes from this form of training. Amongst the benefits reported have been an enhanced confidence with, and understanding of cognitive behavioural theory, an increased appreciation for cognitive behavioural strategies, and greater skill in the application of techniques, including greater flexibility and nuance in their application (Bennett-Levy, 2019; Chigwedere et al, 2019;Collard and Clarke, 2020;Collard and Clarke, 2022;Davis et al, 2015;McGillivray et al, 2015;Scott et al, 2021). Participants also tend to report improved interpersonal skills, allowing for a greater attunement with clients and increased empathy for their presenting difficulties (Bennett-Levy et al, 2015;Chigwedere et al, 2019;McGillivray et al, 2015;Thwaites et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…With the self-practice aspect of the SP/SR framework, trainees are required to practise formulation skills in relation to their own problems, to develop and apply interventions to these, and to then reflect upon what is learnt from these (Bennett-Levy et al, 2015). While much of the SP/SR research has looked at outcomes from overall training programs, there have been a few studies that have focused on the learning outcomes from some specific exercises, including thought diaries, exposure tasks, and behavioural experiments (Bennett-Levy, 2003;Collard and Clarke, 2020;Collard and Clarke, 2022). These have shown that the SP/SR exercises can be used to target specific skills around formulation, intervention planning, and for reviewing intervention outcomes.…”
Section: Sp/sr As a Form Of Competency-based Training And Assessmentmentioning
confidence: 99%
See 1 more Smart Citation